Multi-Actors Capability in Meeting Fertilizer Needs in Maros Regency - Andi Fahri Faisal; Badu Ahmad; Muh. Akmal Ibrahim; Muh. Tang Abdullah (Journal of Management and Administration Provision, 2025)
This study aims to analyze the capability of multi-actors in fulfilling fertilizer needs in Maros Regency through the perspective of collaborative governance and public value governance. The fulfillment of subsidized fertilizer needs is not merely a technical issue related to availability and distribution, but also a governance issue involving the interaction of government actors, business actors, citizens, and nonprofit actors in creating collective capability. This study adopts the strategic triangle perspective developed by John M. Bryson, particularly focusing on operational capability within multi-actor governance. The study employs a qualitative approach using phenomenological methods to explore the experiences, perceptions, and awareness of actors involved in fertilizer governance in Maros Regency. Data were collected through in-depth interviews, observation, and documentation involving the Regent of Maros, DPRD members, the Department of Agriculture and Food Security, agricultural extension workers, PT Pupuk Indonesia, PT Lampoko Ternak Indonesia, fertilizer agents, farmer groups, and HKTI Youth Farmers. The findings reveal that the capability of multi-actors in fertilizer governance remains fragmented and unevenly distributed. Government actors possess formal authority and normative capability but face limitations in technical and operational capability, particularly in digital data management, eRDKK implementation, and verification of farmer and land data. Business actors such as PT Pupuk Indonesia demonstrate strong technical and logistical capability, yet their effectiveness is constrained by weak data synchronization with local government institutions. Agricultural extension workers maintain strong relational capability with farmers but lack adaptive and technological competence. Farmers and farmer organizations remain structurally vulnerable because of low administrative capability and limited integration into decision-making processes. This study concludes that fertilizer governance in Maros Regency reflects fragmented capability rather than collaborative capability. Therefore, strengthening relational capability, digital integration, collaborative coordination, and participatory governance are necessary to create effective public value in fertilizer distribution.